DESIGN OF PROCESS PORTAL FOR RAIL CARGO COMPANY - Gasparik, Jozef (Doprava a spoje, 2005)
Process portal supported by the CRM software solution make possible for the railway cargo operator the supporting of the whole transportation and logistics customer's process and orientation to the individual customers requests by the using of the modern information technologies with a view to obtain the loyal customers in a long term.